Managing tomato bacterial wilt through pathogen suppression and host resistance augmentation using microbial peptide - Tiwari, Ishan; Bhojiya, Ali Asger; Jain, Devendra; Kothari, S. L.; El-Sheikh, Mohamed A.; Porwal, Shalini (Frontiers in Microbiology, 2024)
The increasing health and environmental risks associated with synthetic chemical pesticides necessitate the exploration of safer, sustainable alternatives for plant protection. This study investigates a novel biosynthesized antimicrobial peptide (AMP) from Lactiplantibacillus argentoratensis strain IT, identified as the amino acid chain PRKGSVAKDVLPDPVYNSKLVTRLINHLMIDGKRG, for its efficacy in controlling bacterial wilt (BW) disease in tomato (Solanum lycopersicum) caused by Ralstonia solanacearum. Our research demonstrates that foliar application of this AMP at a concentration of 200 ppm significantly reduces disease incidence by 49.3% and disease severity by 45.8%. Scanning electron microscopy revealed severe morphological disruptions in the bacterial cells upon exposure to the AMP. Additionally, the AMP enhanced host resistance by elevating defense enzyme activities, leading to notable improvements in plant morphology, including a 95.5% increase in plant length, a 20.1% increase in biomass, and a 96.69% increase in root length. This bifunctional AMP provides dual protection by exerting direct antimicrobial activity against the pathogen and eliciting plant defense mechanisms. These findings underscore the potential of this biologically sourced AMP as a natural agent for combating plant diseases and promoting growth in tomato crops. To the best of our knowledge, this is the first study to demonstrate the use of a foliar spray application of a biosynthesized microbial peptide as biocontrol agent against R. solanacearum. This interaction not only highlights its biocontrol efficacy but also its role in promoting the growth of Solanum lycopersicum thereby increasing overall agricultural yield.